PENGEMBANGAN GAME LUDO EDUKATIF PADA MATA PELAJARAN INFORMATIKA KELAS VII SMP SEDERAJAT - Raihan Alfiqih, Muhammad; Pratiwi, Rahmi; Maiziani, Fitri; Kurnia, Reni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of Informatics subject on Computer Systems material for class VII D students at MTsN 12 Tanah Datar, where classical completeness only reached 32.14% (average 66.43) below the minimum criteria of 75. This study aims to describe the development process and produce a valid and practical digital educational Ludo game as an Informatics learning medium. This research used the Research and Development (R&D) method with the 4D development model (Define, Design, Develop, and Disseminate). The trial subjects included one material expert validator (Informatics teacher), two media expert validators from Educational Technology lecturers at UNP, and 28 students of class VII D MTsN 12 Tanah Datar as field trial subjects. Data collection used material validation questionnaires, media validation questionnaires, and student practicality response questionnaires. Results showed material validity at 98.75% ("Very Valid"), media validity at 97.14% (Validator I, "Very Valid") and 81.33% (Validator II, "Valid"), and student practicality at 92.85% ("Very Practical"). The educational Ludo game developed using Visual Studio Code is valid and practical as an innovative learning medium to improve student focus, engagement, and conceptual understanding of Computer Systems material.